Quadricuspid Aortic Valve Visualized by Three-Dimensional Transthoracic Echocardiography. (29th September 2011) - Acar, Eser; Sahin, Tayfun; Yılmaz, Irem; Celikyurt, Umut
Abstract : Quadricuspid aortic valve is a rare congenital anomaly that may cause aortic regurgitation. A 77-year-old male patient was referred to our clinic with complaints of stable angina pectoris. We report a case of a quadricuspid aortic valve diagnosed by 3-dimentional transthoracic echocardiography.